Seeing statistics user's guide - McClelland, Gary H.
SeeinSEEING STATISTICS is an online product which addresses the differing learning styles of today's students. It presents the dynamic, visual nature of statistical concepts using interactive and engaging methods based on years of cognitive research and experience. SEEING STATISTICS uses over 150 Java Applets to create an intuitive learning environment and is surrounded by relevant links to examples, exercises, definitions, and search/navigation capabilities. A handbook accompanies SEEING STATISTICS which contains a password, navigation and exercises